Bifid mandibular canals and the factors associated with their presence: a medical computed tomography evaluation in a Taiwanese population. Issue 2 (6th November 2012) - Fu, Earl; Peng, Michelle; Chiang, Cheng‐Yang; Tu, Hsiao‐Pei; Lin, Yaoh‐Shiang; Shen, E‐Chin
Abstract Objectives To examine distribution of bifid mandibular canals in a Taiwanese population and to evaluate factors contributing to the phenomenon. Material and methods Computed tomographic images from 173 subjects (97 females and 76 males) were obtained using a 64‐slice multidetector computerized tomography system, and the presence of bifid mandibular canals, as well as their widths and lengths, was examined. Association of length of bifid canals with possible contributing factors, including gender, age, and side of presentation, as well as size of cross‐sectional bony area of mandible along the long axis of mandibular canal, was evaluated. Results Bifid mandibular canals, with mean values of 10.1 and 0.9 mm in length and width, were found in 53 (30.6%) of 173 patients and 64 (18.5%) of 346 hemi‐mandibles. Bifid canals appeared more frequently and tend to penetrate mandible with greater lengths in males if compared with those in females. When males were compared with females and when mandibles with bifid canals were compared with ones without, the former tend to present with larger bony area at corresponding levels of cross‐sectional plane than the later, respectively. By regression analysis, significant association was found between length of bifid canals and gender, side of hemi‐mandible, and bony area at mid‐zone of mandibular canal. Conclusions Bifid canals were observed in 30.6% of subjects and 18.5% of hemi‐mandibles. Significant association between length of bifid canals and gender, side of hemi‐mandible, and cross‐sectional bony area of mandible was observed.